2020
DOI: 10.2196/18950
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of the Deployment of the Auto-Visual Acute Flaccid Paralysis Detection and Reporting (AVADAR) System for Strengthening Polio Surveillance in Africa From 2017 to 2018: Evaluation Study

Abstract: Background As we move toward a polio-free world, the challenge for the polio program is to create an unrelenting focus on smaller areas where the virus is still present, where children are being repeatedly missed, where immunity levels are low, and where surveillance is weak. Objective This article aimed to describe a possible solution to address weak surveillance systems and document the outcomes of the deployment of the Auto-Visual Acute Flaccid Paral… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 17 publications
(24 reference statements)
0
2
0
Order By: Relevance
“…After excluding 55 studies, 16 articles were selected for review (Supplement). [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36] We used the Preferred Reporting Items for Systematic reviews and Meta-Analyses flow diagram to outline the screening process (Figure). 37 During review, an additional 3 articles found from the reference lists of the articles were also included.…”
Section: Resultsmentioning
confidence: 99%
“…After excluding 55 studies, 16 articles were selected for review (Supplement). [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36] We used the Preferred Reporting Items for Systematic reviews and Meta-Analyses flow diagram to outline the screening process (Figure). 37 During review, an additional 3 articles found from the reference lists of the articles were also included.…”
Section: Resultsmentioning
confidence: 99%
“…Routine AFP surveillance across most African countries has been fraught with challenges, often linked to limited access to hard-to-reach areas, inability of health workers to correctly and accurately identify AFP cases, poor reporting methods, as well as delays and bottlenecks associated with AFP surveillance data reporting(4) (5). The Auto-Visual AFP Detection and Reporting (AVADAR) application (app) is a digital health intervention designed and developed in 2016 by the Bill and Melinda Gates Foundation (BMGF), in conjunction with the World Health Organization (WHO), the Novel-T and the eHealth Africa (eHA) as a supplemental community surveillance system that harnesses SMS technology and automated alerting, and combines it with corresponding investigations by community informants (CIs) who are systematically and geographically selected for improved active case search and reporting of AFP cases (6) (7). The app, installed on the smartphones of health workers and community informants, widens the AFP surveillance network outside that of the priority reporting sites in order to improve the sensitivity and quality of AFP surveillance, more so in areas (particularly districts) with low performance indicators.…”
Section: Introductionmentioning
confidence: 99%